ANALISIS PERBANDINGAN PENGGUNAAN BEKISTING PADA PEKERJAAN MUT PROYEK RUSUN PASPAMPRES IKN - Saraswati, Nina; Masliyah, Masliyah; Riyanto, Sandi Dwi (Rang Teknik Journal, 2026)
The use of conventional formwork and formwork systems in Multi Utility Tunnel (MUT) construction projects has focused on cost efficiency, quality of work results, and implementation time. A case study was conducted on the Paspampres Flats construction project in the Indonesian Capital City (IKN)Abdullah (2024). The analysis involved identifying material, labor, and equipment costs, evaluating the quality of concrete casting, and measuring the duration of installation, casting, and dismantling. The findings indicate that system formwork outperforms conventional formwork across all three aspects. In terms of cost, system formwork is more efficient for large and repetitive projects as it can be reused multiple times and reduces material waste. Rossaty and Safitri (2022)Regarding quality, system formwork produces smoother, more precise concrete surfaces with minimal leakage. From the perspective of time, the modular characteristics of system formwork accelerate installation and dismantling processes. Therefore, the application of system formwork in MUT projects proves to be more optimal and aligns with modern construction efficiency principles, emphasizing faster execution and enhanced structural quality.Keywords: Conventional formwork, system formwork, cost efficiency, concrete quality, project duration, Multi Utility Tunnel (MUT)